3-PARAMETER WEIBULL DISTRIBUTION ESTIMATION BASED ON GM AND SVM - GAO Bin; CAO KeQiang; HU LiangMou; LI ShuGuang (Jixie qiangdu)
Aiming at the fact that the 3-parameter Weibull distribution model is complex and traditional methods have a low accuracy rate in the case of small samples,a new parameter estimation method based on GM-SVM was proposed. Grey model（ GM） and support vector machine（ SVM） were combined in this method. Firstly,to take advantages of location parameter estimation based on GM method. Secondly,making full use of the accurate estimated results based on SVM in small samples.This method is applied to the establishment of a Weibull distribution parameter estimation model based on GM and SVM,and to the reliability life distribution parameter estimation of certain engine blade. The simulation test results show that this model has preferable parameter estimation accuracy,has obvious advantages in small samples. This model can accurately obtain the three parameters of Weibull distribution.